Balance sheet policy uncertainty and its aggregate implications - Stefania D'Amico; Corey M. Feldman (Federal Reserve Bank of Chicago, 2024)
Using textual analysis of the largest dealers' newsletters to their clients, we construct a measure of uncertainty about the Federal Reserve's balance sheet policy (BSP). This measure of uncertainty tends to spike during the introduction of novel aspects of BSP or at its turning points, with the largest spike occurring during the "Taper Tantrum" period. We find that positive shocks to BSP uncertainty increase longer-term Treasury yields, private borrowing costs, private MBS duration, and reduce mortgage refinance volumes. As a result, an increase in BSP uncertainty has contractionary effects similar to those of a monetary-policy tightening shock. Further, post-2008, these effects seem quite different from those of broader monetary policy uncertainty and fiscal policy uncertainty. Overall, our findings suggest that explicit forward guidance about the Fed's balance-sheet path might be warranted.
Keywords: 330; Federal Reserve's Balance Sheet; Uncertainty; Risk Premia; SVAR